Height is a predictor of hamstring tendon length and ACL graft characteristics in adolescents - Martijn Dietvorst; M. C. Marieke van der Steen; Marijn van den Besselaar; Rob PA Janssen (BMC Musculoskeletal Disorders, 2023)
Abstract Background Knowing the potential hamstring tendon length is relevant for planning ligament reconstructions in children and adolescents, as it is not uncommon to encounter small hamstring tendons intraoperatively. The aim of this study is to predict semitendinosus and gracilis tendon length based on anthropometric values in children and adolescents. The secondary aim is to analyse hamstring tendon autograft characteristics in a closed socket anterior cruciate ligament reconstructions and to evaluate the relationship with anthropometric variables. The hypothesis of this study was that height is predictor of hamstring tendon length and thereby graft characteristics. Methods This observational study included two cohorts of adolescents undergoing ligament reconstructions between 2007–2014 and 2017–2020. Age, sex, height and weight were recorded preoperatively. Semitendinosus and gracilis tendon length and graft characteristics were measured intraoperatively. Regression analysis was performed on tendon length and anthropometric values. Subgroup analyses of the closed socket ACL reconstruction were performed and the relation between anthropometric values and graft characteristics were analysed. Results The population consisted of 171 adolescents from 13 to 17 years of age, with a median age of 16 years [IQR 16–17]. The median semitendinosus tendon length was 29 cm [IQR 26–30] and gracilis tendon length was 27 cm [IQR 25–29]. Height was a significant predictor of semitendinosus and gracilis tendon length. Subgroup analysis of the closed socket ACL reconstructions showed that in 75% of the procedure, the semitendinosus tendon alone was sufficient to create a graft with a minimum diameter of 8.0 mm. Conclusions Height is a significant predictor of semitendinosus and gracilis tendon length in adolescents between 13 and 17 years of age and outcomes are similar to data in adults. In 75% of the closed socket ACL reconstructions, the semitendinosus tendon alone is sufficient to create an adequate graft with a minimum diameter of 8 mm. Additional use of the gracilis tendon is more often necessary in females and shorter patients. Level of evidence 3